2013
DOI: 10.1021/ja404425r
|View full text |Cite
|
Sign up to set email alerts
|

Pruning the ALS-Associated Protein SOD1 for in-Cell NMR

Abstract: To efficiently deliver isotope-labeled proteins into mammalian cells poses a main challenge for structural and functional analysis by in-cell NMR. In this study we have employed cell-penetrating peptides (CPPs) to deliver the ALS-associated protein superoxide dismutase (SOD1) into HeLa cells. Our results show that, although full-length SOD1 cannot be efficiently internalized, a variant in which the active-site loops IV and VII have been truncated (SOD1(ΔIVΔVII)) yields high cytosolic delivery. The reason for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 26 publications
1
67
1
1
Order By: Relevance
“…These studies have, in particular, shown that crowding can cause an either upward or downward shift in the stability of folded test proteins, [7][8][9][11][12][13][14][15][16] and the direction of the shift can, in part, be rationalized based on net-charge considerations. 9 The protein of the present study, trp-cage, has a well-defined folded structure but is small and malleable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have, in particular, shown that crowding can cause an either upward or downward shift in the stability of folded test proteins, [7][8][9][11][12][13][14][15][16] and the direction of the shift can, in part, be rationalized based on net-charge considerations. 9 The protein of the present study, trp-cage, has a well-defined folded structure but is small and malleable.…”
Section: Discussionmentioning
confidence: 99%
“…6 Today, experiments are increasingly often performed under more realistic crowding conditions, using concentrated protein solutions [7][8][9][10] or cells. 9,[11][12][13][14][15][16] In these systems, it has been shown that other interactions may dominate over the steric repulsions and lead to a net destabilization of globular proteins. [7][8][9][12][13][14]16 For a fundamental understanding of these effects, there is a need for computational approaches that permit the simulation of folding/unfolding equilibria in the presence of complex biomolecular crowding agents.…”
Section: Introductionmentioning
confidence: 99%
“…inside living cells. 'In-cell' and 'in-lysate' NMR spectroscopy (Danielsson et al 2013(Danielsson et al , 2015Serber et al 2005Serber et al , 2007Smith et al 2013) have developed to a point where new aspects of protein function can be revealed (Banci et al 2013). For instance in a recent study Selenko and co-workers developed an NMR-based methodology that enables quantification of the temporal phosphorylation and de-phosphorylation of short protein segments in cell lysates (Thongwichian et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…I n-cell NMR represents a unique tool for characterizing physiological processes and their alteration in the 'natural' environment, that is, within a live cellular context, with an atomic-level approach [1][2][3][4][5][6][7][8][9] . This level of characterization is necessary to understand the molecular cause of cell malfunction in pathological states and to develop treatments and therapeutic protocols.…”
mentioning
confidence: 99%